Desain Rancang Bangun Ketel Uap Alat Destilasi Minyak Atsiri - Laode Putu Mahardhika; Hendi Saryanto (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
Indonesia has great potential in the development of essential oils due to its abundant natural resources. However, most essential oil distillation processes in Indonesia still rely on conventional steam boilers fueled by wood or biomass, which have low thermal efficiency and produce high emissions. This research focuses on the design development and fabrication of an induction-based steam boiler as an environmentally friendly alternative for essential oil distillation. The study involves conceptual design, material selection, and fabrication processes based on the ASME Boiler and Pressure Vessel Code (BPVC) Section IV and B31.4 standards. This research focuses on the design and manufacturing stages of the tool, while thermal performance analysis will be carried out in further research., and the functional verification stage is planned to be carried out after the boiler fabrication is completed. Through this approach, the developed prototype is expected to be efficient, safe, and practical for essential oil distillation. The outcome of this design is also expected to serve as a reference for future development of induction heating technology in small- and medium-scale essential oil industries in Indonesia.